THE USE THE GENETICALLY DIFFICULTLY INHERITED TRAIT OF PURPLE ROOT COLOR IN BREEDING PROGRAM FOR THE COMPLICATED TRAIT IN RADISH - S. V. Ugarova; A. V. Zelenin (Овощи России, 2017)
The understanding the nature of trait inheritance in any crops is that determines the quality of results in breeding program. According to reference on previous publication, it is known that phenotypic manifestation of purple root color in radish was caused by regulatory interrelationship mechanisms of genetic control that is difficult to be used directly in breeding program. From literature sources and on the basis of their own research work the authors have proven the practice to maintain the trait in generations, and implementations of development of purple radish breeding accessions have been presented. At first stage of breeding program the selection of initial breeding accessions was carried out, where 14 varieties (red x white) were regarded on the basis of top-crosses to obtain F1 and F2 progenies to be analyzed. Thus, four best combinations from crossing were chosen with 100% of hybridity. Through analysis of hybrids for individual progenies the hybrid population F1 of radish ‘Konfeti’ with different root colors was developed. As result of the individual inbreeding selection on seed plants with pigmented stems and the colored flower rim, the stable breeding accession with purple root was obtained. Thus, in breeding practice in radish it was succeeded to obtain the stably inheriting purple root color in radish accessions, variety ‘Siniiy Iniey’.